1989
DOI: 10.1007/bf02555782
|View full text |Cite
|
Sign up to set email alerts
|

Adenosquamous carcinoma of the colon—An immunocytochemical and ultrastructural study

Abstract: This paper presents two cases of adenosquamous carcinoma of the colon and brings to 39 the total number documented in medical literature. The concurrent glandular and squamous differentiation of the tumor cells was demonstrated by immunocytochemistry and electron microscopy. Evaluation of the biologic characteristics of all the reported cases suggests that malignant squamous elements in colonic carcinomas behave more aggressively than their glandular counterparts. In contradistinction from the pure squamous-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
2

Year Published

1995
1995
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 28 publications
1
18
0
2
Order By: Relevance
“…6,8 Some reports have emphasized that the squamous carcinoma component metastasizes more frequently and has a more aggressive behavior than that of glandular metastasis. 13,14 Likewise in our case, the survival after operation was only 14 months. Although the behavior of colorectal adenosquamous carcinoma is aggressive, the mechanism of occurrence for this neoplasm has yet to be sufficiently explained.…”
Section: Case Reportmentioning
confidence: 64%
“…6,8 Some reports have emphasized that the squamous carcinoma component metastasizes more frequently and has a more aggressive behavior than that of glandular metastasis. 13,14 Likewise in our case, the survival after operation was only 14 months. Although the behavior of colorectal adenosquamous carcinoma is aggressive, the mechanism of occurrence for this neoplasm has yet to be sufficiently explained.…”
Section: Case Reportmentioning
confidence: 64%
“…The squamous cell component has been reported to have a greater metastatic potential than the glandular cell component, and it has also been detected at metastatic sites. 6 The metastatic lymph nodes in our case contained squamous cells (Fig. 2c).…”
Section: Discussionmentioning
confidence: 91%
“…As regards the basaloid variety of squamous cell carcinoma outside the anal canal, it may arise from cloaco- genic embryologic nests, squamous metaplastic epithelium, or totipotential basal cells [12]. In mixed adenosquamous variety, Cerezo and others suggested that all such lesions be carefully evaluated by means of immunoperoxidase stains and/or electron microscopy in order to identify squamous features [20,21]. Symptoms, investigations, and assessment of patients with the divergent histologic subtypes of squamous cancer of the colon and rectum, including basaloid tumors, are similar to those of colon adenocarcinoma, as is evident in our case [5,22].…”
Section: Discussionmentioning
confidence: 99%